Process Evaluation of the Deployment of Service Attachés or Representatives of Certain Government Agencies - Julio S. Amador; Maria Gisela B. Orinion; Mary Ann L. Del Rosario; Jill Angeli V. Bacasmas (Philippine Institute for Development Studies (PIDS), 2022)
This Study on Process Evaluation of the Deployment of Service Attachés or Representatives of Certain Government Agencies evaluates the deployment processes of service attachés of eight (8) government agencies1 . It reviews the current systems, frameworks and criteria in place for the deployment of service attachés at the relevant Partner Agencies and the Department of Foreign Affairs that are based on laws and policies (i.e., agency-specific and interagency). Further, it reviews the monitoring and evaluation systems in place that have captured the measurable outputs and performance of the deployed service attachés. Findings validate that the processes involved in the deployment of service attachés are based on policies [i.e. Department Orders, Administrative Orders (AO) and Joint Circulars] of the concerned Partner Agencies and are governed by legal bases [i.e., Executive Order (EO) 2922 , EO 74, series of 1993, and the Philippine Foreign Service Act of 1991 or Republic Act (RA) 7157]. While Laws3 and policies4 for a uniform rules and regulations on assignments at Foreign Service Posts (FSP)5 exist, Partner Agencies have varying degrees of policy consistencies (i.e., creation of a selection committee for recruitment of service attachés, roster or rotation pool, etc.) and discrepancies in the implementation of their own policies (i.e., length of stay at FSPs). On the other hand, the monitoring and evaluation systems of the Partner Agencies proved to be a challenge to obtain. While some of the government agencies' home service units confirmed the existence and submission of performance and evaluation reports by service attachés or Heads of Post, actual samples of these said reports were not received. Thus, this Study opens further research on the examination of the service attachés' performance and evaluation reports, a review of its content, and an analysis of their outputs vis-à-vis the government agencies' budget costs.
Keywords: 330; budget; foreign service; performance evaluation; service attachés